Bioinspired Diatomite Membrane with Selective Superwettability for Oil/Water Separation - Yu-Hsiang Lo (Nature Portfolio, 2017)
Abstract Membranes with selective superwettability for oil/water separation have received significant attention during the past decades. Hierarchical structures and surface roughness are believed to improve the oil repellency and the stability of Cassie-Baxter state. Diatoms, unicellular photosynthetic algae, possess sophisticated skeletal shells (called frustules) which are made of hydrated silica. Motivated by the hierarchical micro- and nanoscale features of diatom, we fabricate a hierarchical diatomite membrane which consists of aligned micro-sized channels by the freeze casting process. The fine nano-porous structures of frustules are well preserved after the post sintering process. The bioinspired diatomite membrane performs both underwater superoleophobicity and superhydrophobicity under various oils. Additionally, we demonstrate the highly efficient oil/water separation capabililty of the membranes in various harsh environments. The water flux can be further adjusted by tuning the cooling rates. The eco-friendly and robust bioinspired membranes produced by the simple, cost-effective freeze casting method can be potentially applied for large scale and efficient oil/water separation.